2015
DOI: 10.1200/jco.2015.33.15_suppl.e20645
|View full text |Cite
|
Sign up to set email alerts
|

Oncology providers' perspectives on endocrine therapy prescribing and management.

Abstract: Purpose: Adjuvant endocrine therapy (ET) can reduce the risk of recurrence among females with hormone receptor-positive breast cancer. Overall, initiation and adherence to ET are suboptimal, though reasons are not well described. The study's objective was to better understand ET decision making, prescribing, and patient management from oncology providers' perspectives. Methods: Using purposive sampling, we recruited oncology providers who saw five or more breast cancer patients per week (n=20). We conducted 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 18 publications
(26 reference statements)
0
15
0
Order By: Relevance
“…Overcoming the burden of numerous in-office visits, the increase in successful telehealth visits during the COVID-19 pandemic [60] has demonstrated that virtual platforms can be a means for these discussions. An in-person or virtual visit just prior to treatment initiation could overcome the finding that many patients do not remember having detailed discussions about potential ET-related side effects and may serve to reinforce that ET is just as important a component of treatment as surgery, chemotherapy, or radiation therapy [20,30,61]. Intermittent telehealth visits could also address patient decision resolve, as many patients re-visit their commitment to continue ET multiple times throughout the course of treatment [2].…”
Section: Discussionmentioning
confidence: 99%
“…Overcoming the burden of numerous in-office visits, the increase in successful telehealth visits during the COVID-19 pandemic [60] has demonstrated that virtual platforms can be a means for these discussions. An in-person or virtual visit just prior to treatment initiation could overcome the finding that many patients do not remember having detailed discussions about potential ET-related side effects and may serve to reinforce that ET is just as important a component of treatment as surgery, chemotherapy, or radiation therapy [20,30,61]. Intermittent telehealth visits could also address patient decision resolve, as many patients re-visit their commitment to continue ET multiple times throughout the course of treatment [2].…”
Section: Discussionmentioning
confidence: 99%
“…Although due to the correlative nature of the data, we cannot answer the question whether patients discontinue treatment because they expect their management to be ineffective or whether they discontinue first and rationalize their behavior thereafter, our findings nonetheless reinforce the importance of side-effect coping in AET. Its pivotal role considering adherence optimization has also been pointed out by both patients [ 46 , 48 ] and practitioners [ 49 ] in prior qualitative studies. Furthermore, in a trial of cognitive-behavioral therapy for vasomotor symptoms of breast cancer survivors, beliefs about coping and control of hot flushes were found to be the main mediator of how burdensome symptoms were perceived after the therapy [ 10 ].…”
Section: Discussionmentioning
confidence: 98%
“…We used ET‐specific survey questions assessing reasons for ET non‐adherence (See online supplemental materials). These questions were based on existing medication adherence intruments and previous qualitative assessments of reasons for ET non‐adherence . Questions were cognitively tested with 12 breast cancer patients and revised iteratively based on patient input.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have evaluated the extent of ET non‐adherence in self‐report or claims data and have assessed reasons for non‐adherence qualitatively . Qualitative studies highlight a need to improve provider communication, particularly around the benefit of ET in recurrence risk reduction and need to help patients to better manage potential ET side effects .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation